PERAN MOTIVASI DALAM MENINGKATKAN KEBERHASILAN HAFALAN AL-QUR’AN SANTRI DI PONDOK TAHFIDZUL QUR’AN AT-TAUBAH - Hafinas; Fathiya; Frisca; Muhd.Riduwan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Motivation is a psychological factor that plays an important role in supporting students’ success in memorizing the Qur’an. This study aims to examine the role of motivation in improving the success of Qur’an memorization among students at At-Taubah Tahfidzul Qur’an School. This research employs a qualitative approach with a descriptive research design. Data were collected through observation, interviews, and documentation involving students and tahfidz mentors as research subjects. The results show that intrinsic motivation, such as spiritual awareness, the desire to gain Allah SWT’s pleasure, and the drive to preserve the purity of the Qur’an, contributes significantly to students’ perseverance in memorization. In addition, extrinsic motivation derived from the school environment, the role of mentors, peer support, and a structured coaching system also strengthens the consistency and quality of students’ memorization. A conducive and religious learning environment further supports the internalization of motivation